Respiratory dialysis for avoidance of intubation in acute exacerbation of COPD - Mani, Raj Kumar; Schmidt, Werner; Lund, Laura W.; Herth, Felix (ASAIO journal, 2013)
Noninvasive ventilatory support has become the standard of care for patients with chronic obstructive pulmonary disease (COPD) experiencing exacerbations leading to acute hypercapnic respiratory failure. Despite advances in the use of noninvasive ventilation and the associated improvement in survival, as many as 26% of these patients fail noninvasive support and have a higher subsequent risk of mortality than patients treated initially with invasive mechanical ventilation. We report the use of a novel device to avoid invasive mechanical ventilation in two patients who were experiencing acute hypercapnic respiratory failure because of an exacerbation of COPD and were deteriorating, despite support with noninvasive ventilation. This device provided partial extracorporeal carbon dioxide removal at dialysis-like settings through a single 15.5 Fr venovenous cannula inserted percutaneously through the right femoral vein. The primary results were rapid reduction in arterial carbon dioxide and correction of pH. Neither patient required intubation, despite imminent failure of noninvasive ventilation before initiation of extracorporeal support. Both patients were weaned from noninvasive and extracorporeal support within 3 days. We concluded that low-flow extracorporeal carbon dioxide removal, or respiratory dialysis, is a viable option for avoiding intubation and invasive mechanical ventilation in patients with COPD experiencing an exacerbation who are failing noninvasive ventilatory support.
Gesehen am 22.06.2021